The relationship between ESG scores and financial performance : a bi-directional analysis : evidence form the UK - Santos, André Grácio (2023)
This thesis investigates the relationship between Environmental, Social, and Governance (ESG) performance and financial performance (FP). Specifically, we aim to analyse a potential bi-directional causality between a firm’s ESG performance and financial performance. A dataset of 472 firms listed on the London Stock Exchange (LSE) and Alternative Investment Market (AIM) from 2010 to 2021 (11-year period) is used (2,914 firm-year observations). Both accounting and market-based measures measure financial performance, Return on Assets (ROA) and Price to Book Value Ratio (PBV), respectively. ESG performance scores are obtained from Thomson Reuters’ Refinitiv DataStream. Conducting Ordinary Least Squares (OLS) and Fixed-Effects (FE) regression models, the findings suggest that there is no significant impact of ESG performance on ROA and PBV, both at one-year and two-year lags. We find one-year lagged ROA to negatively affect ESG performance, while no significant causal effect of lagged PBV on subsequent ESG performance is observed, which reveals mixed results. Regarding the control variables, we find strong evidence indicating a positive impact of risk and firm size on subsequent ESG performance. This study furthers understanding of the interaction between ESG performance and financial performance of firms within the UK context over a long-term period.